1989
DOI: 10.1007/bf01255817
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma prostaglandin E2 levels in schizophrenia

Abstract: Plasma levels of prostaglandin E2 (PGE2) were determined with radioimmunoassay in 40 DSM-III schizophrenics, 15 patients with other mental disorders, and 23 normal controls. The mean value of plasma immunoreactivity of PGE2 was significantly higher in the schizophrenic patients than in the normal controls. Schizophrenic patients with high plasma PGE2 levels had more guilt feelings and hallucinatory behavior on BPRS, relatively successful heterosexual relations, and a higher incidence of birth complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 26 publications
(25 reference statements)
1
20
0
4
Order By: Relevance
“…Several studies demonstrated the type-2 inducing effect of PGE 2 -the major product of COX-2, while inhibition of COX-2 is accompanied by inhibition of type-2 cytokines and induction of type-1 cytokines (Pyeon et al, 2000;Stolina et al, 2000). PGE 2 levels in schizophrenia have not been well studied; increased levels of PGE 2 , however, have been described (Kaiya et al, 1989). PGE 2 , however, induces the production of IL-6, a cytokine which is consistently described to be increased in schizophrenia (see above).…”
Section: The Possible Role Of Kyna In Schizophreniamentioning
confidence: 96%
See 2 more Smart Citations
“…Several studies demonstrated the type-2 inducing effect of PGE 2 -the major product of COX-2, while inhibition of COX-2 is accompanied by inhibition of type-2 cytokines and induction of type-1 cytokines (Pyeon et al, 2000;Stolina et al, 2000). PGE 2 levels in schizophrenia have not been well studied; increased levels of PGE 2 , however, have been described (Kaiya et al, 1989). PGE 2 , however, induces the production of IL-6, a cytokine which is consistently described to be increased in schizophrenia (see above).…”
Section: The Possible Role Of Kyna In Schizophreniamentioning
confidence: 96%
“…In schizophrenia, however, the data on Prostaglandin E 2 (PGE 2 ) are not conclusive: while in several elder studies increased blood levels of PGE 2 were described (Kaiya et al, 1989), a more recent study found no increase of PGE 2 levels in the CSF of schizophrenics (Nishino et al, 1998). There are indications that the PGE 2 level might be related to the actual psychopathology (Kaiya et al, 1989).…”
Section: Pge 2 Inflammation and Immune Dysbalancementioning
confidence: 96%
See 1 more Smart Citation
“…Elevated serum and/or plasma levels of pro-inflammatory factors like prostaglandin E2 (PGE 2 ) [13], C-reactive protein (CRP) [14], IL-1β and TNF-α [15] have been found in schizophrenic individuals. Furthermore, high microglial activation in the brain of schizophrenic patients has been reported in postmortem studies [16,17].…”
mentioning
confidence: 99%
“…To elaborate, elevated levels of PGE 2 , a signalling molecule, were associated with SCZ and symptom severity. 73 In addition, a beneficial effect on treatment outcome of cyclooxygenase-2 (COX-2) inhibitor add-on treatment to risperidone was observed. 74 Inhibition of COX-2, an upstream regulator of PGE 2 , is expected to reduce PGE 2 levels.…”
Section: Drd3 Polymorphisms and Clozapine Responsementioning
confidence: 98%